Providing information and detecting concerns about health in general practice populations using a computer system in the waiting area. - Stanley, I; Tongue, B (British Journal of General Practice, 1991)
Theoretical and practical problems for general practice exist following the increased emphasis placed upon preventive care in the 1990 contract for general practitioners. In particular, the risk that questionable systematic activity is encouraged while opportunistic prevention is discouraged, suggests the need for better targeted and more efficient methods of health promotion. This paper describes computer software which provides a broad range of information about health on a patient-dedicated terminal in general practice waiting areas. The software is interactive and monitors both the level of use of the component parts of the database and specific information sought but not found. In this way the system generates an indicator of 'health concerns' in the practice population. Experience of the system at four contrasting sites in Merseyside is reported. Data from the first year suggest that site-specific differences in use and perceived need are emerging, and could lead to an information source which evolves in response to local demand. In addition, the system should provide a resource for opportunistic prevention in primary care and a way of monitoring the emergence of new concerns about health.